Spectroscopic studies of the unfolding of a multimeric protein α‐crystallin. Issue 5 (May 2014) - Chowdhury, Aritra; Choudhury, Aparajita; Banerjee, Victor; Banerjee, Rajat; Das, K. P.
ABSTRACT α‐Crystallin is a multimeric eye lens protein having molecular chaperone‐like function which is crucial for lens transparency. The stability and unfolding‐refolding properties of α‐crystallin plays important roles for its function. We undertook a multi probe based fluorescence spectroscopic approach to explore the changes in the various levels of organization of this protein at different urea concentration. Steady state fluorescence studies reveal that at 0.6M urea a compact structural intermediate is formed which has a native‐like secondary structure with enhanced surface exposure of hydrophobic groups. At 2.8M urea the tertiary interactions are largely collapsed with partial collapse of secondary and quaternary structure. The surface solvation probed by picosecond time resolved fluorescence of acrylodan labeled α‐crystallin revealed dry native‐like core of α‐crystallin at 0.6M urea compared to enhanced water penetration at 2.8M urea and extensive solvation at 6M urea. Activation energy for the subunit exchange decreased by 22 kJ mol−1 on changing urea concentration from 0 to 0.6M compared with over 75 kJ mol−1 on changing urea concentration from 0 to 2.8M. Light scattering and analytical ultracentrifugation techniques were used to determine size and oligomerization of the unfolding intermediates. The data indicated swelling but no oligomer breakdown at 0.6M urea. At 2.8M urea the oligomeric size is considerably reduced and a monomer is produced at 6M urea. The data clearly reveals that structural breakdown of α‐crystallin does not follow hierarchical sequence as tertiary structure dissolution takes place before complete oligomeric dissociation. © 2013 Wiley Periodicals, Inc. Biopolymers 101: 549–560, 2014.